Program promotif poskestren terhadap PHBS santri di pondok pesantren - Lalu Dedy Supriatna; Indasah Indasah; Byba Melda Suhita (Holistik Jurnal Kesehatan, 2020)
Pesantren Health Post (Poskestren) promotional program for Clean and Healthy Living Behavior (CHLB)  among students at Islamic boarding schoolsBackground: Clean and Healthy Living Behavior (CHLB) school environment structure is an effort to empower students, teachers, and the school community to know, want, and be able to treat CHLB. This is in line with Health Promotion in educational institutions (Health Promoting School) launched by the World Health Organization which uses a holistic model that includes the relationship between physical, mental, social and environmental aspects.Purpose: To analyze the influence of the health post promotion program for Clean and Healthy Living Behavior (CHLB)  among students at Islamic boarding schoolsMethod: An observational analytic study using a cross sectional approach. The sampling technique used simple random sampling, a sample of 271 respondents. The research instrument used a questionnaire with 20 question items. The data analysis technique used the chi-square test.Results: Obtained from 271 respondents with the Poskestren program (Promotive) in the less category, it will have an influence in the moderate category on the (CHLB)   of students (36.16%). It is necessary to plan that is directed and sustainable in improving the quality for the implementation of the poskestren program in a promotional manner so that it can get better results.Conclusion: The Pesantren Health Post program promoted a significant effect on (CHLB)  among students at Ad Diinul Qayyim Islamic Boarding School, West Lombok Regency, NTB.Keywords: Pesantren Health Post (Poskestren); Promotional program; Clean and Healthy Living Behavior (CHLB); Students; Islamic boarding schoolsPendahuluan: Perilaku Hidup Bersih dan Sehat (PHBS) tatanan lingkungan sekolah adalah upaya untuk memberdayakan siswa, guru, dan masyarakat lingkungan sekolah agar tahu, mau, dan mampu memperlakukan PHBS. Hal ini sejalan dengan Promosi Kesehatan di institusi pendidikan (Health Promoting School) yang dicanangkan oleh Organisasi Kesehatan Dunia yang menggunakan model holistik yang meliputi hubungan antar aspek fisik, mental, sosial, dan lingkungan.Tujuan: Untuk menganalisis pengaruh program promotif  poskestren terhadap PHBS Santri di Pondok PesantrenMetode: Penelitian analitik observasional dengan menggunakan pendekatan cross sectional. Teknik sampling menggunakan simple random sampling, sampel sebanyak 271 responden. Instrumen penelitian menggunakan kuisioner dengan 20 item pertanyaan. Teknik analisa data menggunakan uji chi-square.Hasil: Didapatkan dari 271 responden dengan program Poskestren (Promotif) dalam kategori kurang maka akan memberikan pengaruh dalam kategori cukup pada PHBS santri (36.16%). Perlu perencanaan yang terarah dan berkesinambungan dalam meningkatkan kualitas untuk penerapan program poskestren secara promotif sehingga mendapatkan hasil yang lebih baik.Simpulan: Program Poskestren secara promotif berpengaruh secara signifikan terhadap PHBS pada santri di Pondok Pesantren Ad Diinul Qayyim Kabupaten Lombok Barat NTB.